Counseling on Elderly about Gymnastics to Improve Sleep Quality of The Elderly - Endah Purwanti Handayani; Susi Lestari; Eftyaningrum Dwi Wahyu Astutik; Tiyan Febriyani Lestari; Wiwit Vitania; Harlinda Widia Putri; Hasnia; Yustika Rahmawati Pratami; Siti Saldianti; Yuliana Antoneta Apaseray; Silpa Daap; Emeliana Amyol; Senita Karoba; Anice Mallo; Welmince Kwano (Journal of Community Service for Health, 2023)
Elderly (elderly) is the final stage of development in the human life cycle which is a natural process that cannot be avoided, runs continuously, and continuously. As they get older, the elderly certainly experiences changes physically, psychologically, socially and spiritually. The cause of these changes can interfere with sleep quality. The level of physical ability that has decreased is very influential on the quality of sleep of the elderly. The purpose of this community service was to convey important information to maintain health for the elderly by routinely carrying out sports such as elderly gymnastics, so that the elderly can carry out normal activities. The method was counseling for the population group of all elderly at the Sereh Village Posyandu as many as 32 people. The result showed that there was an increase in knowledge about the elderly.